PENGARUH GAYA KEPEMIMPINAN DAN KEADILAN PERSEPSIAN TERHADAP PENCIPTAAN BUDGETARY SLACK (Studi Empiris Pasa Perusahaan Manufaktur di Magelang) - Yuliani, Nur Laela; Widyaningrum, Goenarsih (Jurnal Analisis Bisnis Ekonomi, 2006)
Research concerning budget participation with budgetary slack have come to interesting issue for many researchers. This research will test tendency of subordinates in creating budgetary slack which do not only relating to economic factor like in theory of agensi traditionally. This study will use sactor of organizational social factor and in testing influence of creation of budgetary slack that is leadership style and justice of percepsian. Factor of organizational use leadership style, partisipative leadership style can lessen behavior of manager disfungsional that is creation of budgetary slack. Social factor evaluated from side perception of manager of justice of persepsian. In perpective justice of persepsian can be seen from distribute justice and justice of prosedural. Perception of manager formed because individual interaction in an group to make decision to with. Individual evaluation of organizational outcome and budgeting process in partisipative budgeting become base acceptance of individual to justice. Target of this research is to lay open empirically influence of leadership style and justice of persepsian in influencing creation of budgetary slack. Result of this research good for adding literature in partisipative budgeting area. Analysis the used is doubled linear regression analysis. Test of R used to know the level of independent variable contribution in influencing variable of dependen, while hypothesis test the used is test of F and test t. This research result is obtained evidence that leadership atyle have an effect on to creation of budgetary slack. Justice of low persepsian high will degrade (highest) creation of budgetary slack. Manager with high leadership style, justice of high persepsian will boost up creation of budgetary slack. Manager with low leadership style, justice of low persepsian will degrade creation of budgetary slack.